Pump and signal power combiners for high-power fiber amplifiers applications - Sliwinska, Dorota; Kaczmarek, Pawel; Abramski, Krzysztof Marek (Photonics Letters of Poland, 2015)
In this work we present our result on investigation of pump power combiner fabrication process in configuration (N+1)x1. Our fabrication method is based on tapering of fiber bundle consisting of 6 multimode fibers and one signal fiber. We present results on fabrication power combiners based on single mode fibers and large mode area fibers for the signal. Full Text: PDF References D. Noordegraaf et al., "All-fiber 7x1 signal combiner for incoherent laser beam combining", Proc. SPIE 7914 79142 (2011) CrossRef E. Snitzer, H. Po, F. Hakimi, R. Tumminelli, B. C. McCollum,"Double Clad Offset Core Nd Fiber Laser", Opt. Fiber Sensor Topical Meeting., New Orleans, LA, 1988. CrossRef Zervas, M.N., Codemard, C.A., "High Power Fiber Lasers: A Review," Selected Topics in Quantum Electronics, IEEE Journal of, vol.20, no.5, pp.219,241, Sept.-Oct. 2014 CrossRef F. Hakimi, H. Hakimi, "New side coupling method for double-clad fiber amplifiers", Lasers and Electro-Optics, 2001. CLEO '01. Technical Digest. Summaries of papers presented at the Conference on, pp.116, 11-11 May 2001. CrossRef J.P. Koplow, S.W. Moore, D.A.V. Kliner, "A new method for side pumping of double-clad fiber sources", IEEE Journal of Quantum Electronics, 39, 4, Apr 2003. CrossRef Ch. Li, D. Shen, J. Song, N. S. Kim, K. Ueda, "Absorption characteristics of high-power disc fiber laser by side pumping of laser diode", Lasers and Electro-Optics. CLEO/Pacific Rim '99, 3 (1999). CrossRef J. Swiderski, A. Zając, M. Skorczakowski, "Pulsed ytterbium-doped large mode area double-clad fiber amplifier in MOFPA configuration", Opto-Electronics Review, 15, 2, (June 2007). CrossRef Y. Jeong, et al., "40-Gb/s Widely Tunable Transceivers", IEEE Journal of Selected Topics In Quantum Electronics, 13, 3 (May/June 2007). CrossRef W. Shi, Q. Fang, X. Zhu, R. A. Norwood, N. Peyghambarian, "Fiber lasers and their applications", Applied Optics 53, 28 (2014). CrossRef D. J.Richardson, J. Nilsson, and W. A. Clarkson, "High power fiber lasers: current status and future perspectives", J. Opt. Soc. Am. B 27, 11 (2010). CrossRef F. Gonthier et al., "High-Power all-fiber components: The missing link for high power fiber lasers", Fiber Lasers: Technology, Systems and Applications, 266-276, (2004). CrossRef A. Braglia, A. Califano, Y. Liu and G. Perrone, "Architectures and components for high power CW fiber lasers", International Journal of Modern Physics B, 28, 12 (2014). CrossRef G. Sobon, P. Kaczmarek, D. Sliwinska, J. Sotor, K. Abramski, "High-Power Fiber-Based Femtosecond CPA System at 1560 nm", IEEE Journal of Selected Topics in Quantum Electronics, 20, 5 (2014). CrossRef D. J. DiGiovanni, and A. J. Stentz, "Tapered fiber bundles for coupling light into and out of cladding-pumped fiber devices", U.S. Patent 5,864,644 A, Jan. 26, (1999). DirectLink A. Braglia, A. Califano, Y. Liu and G. Perrone, "Architectures and components for high power CW fiber lasers", International Journal of Modern Physics B, 28, 12 (2014). CrossRef J. K. Kim et al., "Monolithic all-glass pump combiner scheme for high-power fiber laser systems", Optics Express, 18, 12, (24 May 2010). CrossRef B. Sévigny, P. Poirier, M. Faucher, "Pump combiner loss as a function of input numerical aperture power distribution", Proc. SPIE 7195, 719523 (2009) CrossRef A. Kosterin, V. Temyanko, M. Fallahi,M. Mansuripur, "Tapered fiber bundles for high power applications", Technical Digest. OFC/NFOEC 2 (2005) CrossRef P. Koška, Y. Baravets,P. Peterka, J. Bohata, M. Písařík, "Mode-field adapter for tapered-fiber-bundle signal and pump combiners", Applied Optics, 54, 4 (1 February 2015) CrossRef R. Wiley, B. Clark, "High-power fused assemblies enabled by advances in fiber-processing technologies", Proc. SPIE 7914, 79140F (2011). CrossRef